Next generation artificial vision systems : reverse engineering the human visual system - Bharath, A. A. (Anil Anthony); Petrou, Maria (Artech House bioinformatics & biomedical imaging series., 2008)
This interdisciplinary work brings you to the cutting edge of emerging technologies inspired by human sight, ranging from semiconductor photoreceptors based on novel organic polymers and retinomorphic processing circuitry to low-powered devices that replicate spatial and temporal processing in the brain. Moreover, it is the first work of its kind that integrates the full range of physiological, engineering, and mathematical issues and advances together in a single source.